A synergistic multitargeted of BET and HDAC: an intra-molecular mechanism of communication in treatment of Waldenström macroglobulinemia. Issue 3 (11th February 2022) - Elamin, Ghazi; Aljoundi, Aimen; Soliman, Mahmoud E.S.
ABSTRACT: Preclinical evidence suggests effectiveness of the combined inhibition of bromodomain and extra-terminal (BET) and histone deacetylase (HDAC) proteins in the treatment of Waldenström macroglobulinemia (WM). However, toxicity, dosing scheduling, and drug–drug interactions are common challenges in combined therapy. In this article, we scrutinise the potential synergistic effect of a dual acting anti-cancer therapy using a single drug TW22 that concomitantly inhibits BET/HDAC proteins, which may open a new line of therapeutic protocol in the treatment of Waldenström macroglobulinemia (WM). The preferential binding mechanisms of the dual inhibition of BET/HDAC enzymes have been a subject of debate in literature. In this report, molecular dynamic simulations coupled with other advanced biocomputational tools were applied to investigate the preferential binding modes and the conformational implications of dual inhibition of both BET/HDAC enzymes. Intriguingly, findings show that multitarget TW22 have superior binding affinity by16.2% and 39.8% than BET/HDAC parent inhibitor molecules JQ1 and Panobinostat, respectively. This disparity has also resulted in higher protein stability and prominent correlated motions were observed with the least fluctuations and multiple van der Waals interactions. The findings of this study will aid in the design of improved anti-cancer agents, thus allowing for increased patient adherence.